Estimation of the Optimal Futures Hedge - Cecchetti, Stephen G.; Cumby, Robert E.; Figlewski, Stephen (The Review of Economics and Statistics, 1988)
Standard approaches to designing a futures hedge often suffer from two major problems. First, they focus only on minimizing risk, so no account is taken of the impact on expected return. Second , in estima ting the hedge ratio, no allowance is made for time variation in the distribution of cash and futures price changes. This paper describes a technique for estimating the optimal futures hedge that corrects these problems and illustrates its use in hedging Treasury bonds with T-bond futures. Copyright 1988 by MIT Press.